The Need of a Network Approach in Household Waste Packages Collection: An Empirical Analysis in a Heteorgenous Population Density Area - Menezes, J.; Crespo de Carvalho, J.; Dias, E.B.; Martins, A. (ICIL 2003, 2003)
The physical flow doesn't finish with the consumption. Another flow begins after the consumption and different logistics activities have to be performed to guarantee a superior service level and to reintroduce in the manufacturing/packaging activity the recovered packages/materials. Many authors have written about this topic (ex. Marianne Jahre, 1995) and have focused their analysis in the channel theory (speculation vs. postponement). In our research we analysed the Portuguese context, and the need of a network approach to this topic. Although, our main objective in this research was to identify the variables that influence the household packages recovery logistics performance, focusing in the drop-off and door-to-door systems. After that, we have developed a framework analysis (composed by a set of KPI's) to classify the different systems. We have considered the productivity (tons/hour; tons/km, among others), the average time by circuit, among others items. Thus, we have applied the framework in a heterogeneous population density area (Loures Lisbon), where the different household waste recovery systems have been implemented. With this empirical approach, applying the case study method, we have achieved to our main conclusion: the door-to-door system (named kerbside model) has an impact on quantities deposited and collected, and, improve the efficiency of the reverse logistics systems.